pyGABEUR-ITB: A FREE SOFTWARE FOR ADJUSTMENT OF RELATIVE GRAVIMETER DATA - Wijaya, Dudy Darmawan; Muhamad, Norman Arif; Prijatna, Kosasih; Pahlevi, Arisauna; Putra, Widy; Sadarviana, Vera; Sarsito, Dina A.; Variandy, Erfan D. (GEOMATIKA, 2019)
pyGABEUR-ITB (Python GayaBEUrat Relatif – Institut Teknologi Bandung) is a free and interactive software for adjustment of relative gravimeter data, developed based on Python programming language. pyGABEUR-ITB can adjust relative gravity measurements and provide reliable estimates for correcting instrument’s systematic errors, such as gravimeter drift. Furthermore, pyGABEUR-ITB can also detect possible outliers in the observations using the t-criterion method. Since pyGABEUR-ITB is using the weighted constraint adjustment, at least one fixed station is required accordingly. Relative gravimeter data around Palu-Donggala area (Central Sulawesi) observed by Center for Geodesy Control Networks and Geodynamics, Geospatial Information Agency, were used to test the performance of pyGABEUR-ITB. The processing results were then compared against those calculated using GRAVNET software. The comparisons show that both pyGABEUR-ITB and GRAVNET softwares statistically provide simillar results, with the total RMS value of about 5 mGal. In term of computer’s requirement, pyGABEUR-ITB can be excecuted under a computer with the following minimal requirements: x64 CPU, 1 GB memory and WINDOWS 7 OS. Finally, it is important to mention that pyGABEUR-ITB is recently suited to process the data from the gravimeter that adopts the principle of vertical spring balance. In the near future, pyGABEUR-ITB will be extended to be able to automatically adapt to various observation principles.